1997
DOI: 10.1093/jpepsy/22.3.399
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Validation of the Children’s Hope Scale

Abstract: Assuming that children are goal-oriented, it is suggested that their thoughts are related to two components--agency and pathways. Agency thoughts reflect the perception that children can initiate and sustain action toward a desired goal; pathways thoughts reflect the children's perceived capability to produce routes to those goals. Hope reflects the combination of agentic and pathways thinking toward goals. A six-item dispositional self-report index called the Children's Hope Scale is introduced and validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
715
4
17

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 906 publications
(765 citation statements)
references
References 13 publications
29
715
4
17
Order By: Relevance
“…Accordingly, one must not apply the results to male college athletes until such studies are completed. In previous studies with over 5,000 college students, however, there has never been a gender difference in Hope Scale scores among college students (see Snyder, 1994b;Snyder, Harris, etal., 1991) or teenagers (Snyder, Hoza, et al, 1997). This lack of previous gender effects does not preclude, of course, the possibility of such differences occurring in future male and female samples of college athletes.…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, one must not apply the results to male college athletes until such studies are completed. In previous studies with over 5,000 college students, however, there has never been a gender difference in Hope Scale scores among college students (see Snyder, 1994b;Snyder, Harris, etal., 1991) or teenagers (Snyder, Hoza, et al, 1997). This lack of previous gender effects does not preclude, of course, the possibility of such differences occurring in future male and female samples of college athletes.…”
Section: Discussionmentioning
confidence: 97%
“…Children's dispositional hope was examined through the Children's Hope Scale for ages 8 to 16 (Snyder, Hoza, et al, 1997) which comprises three agency thinking (e.g., "I think I am doing pretty well") and three pathways thinking (e.g., "I can think of many ways to get the things in life that are most important to me") items. Responses ranged from 1 = None of the time to 6 = All of the time.…”
Section: Methodsmentioning
confidence: 99%
“…However, few studies have examined hope among children and adolescents aside from samples used during the initial validation of the Children's Hope Scale (CHS: see Snyder et al 1997), and that of two studies which aimed to further validate the CHS with middle and high school students (see Valle et al 2004). Expanding on previous hope work, investigated various psychoeducational and psychological indicators of school adjustment and their relationships to adolescent students' levels of hope and found that both the Pathways and Agency subscales of the CHS were positively correlated to global LS, personal adjustment, grade point average (GPA), and SEAs, but negatively correlated to indicators of psychological distress, and school maladjustment.…”
Section: Hopementioning
confidence: 99%